Sarcocystis nesbitti causes acute, relapsing febrile myositis with a high attack rate: description of a large outbreak of muscular sarcocystosis in Pangkor Island, Malaysia, 2012. - Claire M Italiano; Kum Thong Wong; Sazaly AbuBakar; Yee Ling Lau; Norlisah Ramli; Sharifah Faridah Syed Omar; Maria Kahar Bador; Chong Tin Tan (Public Library of Science (PLoS), 2014)
BACKGROUND: From the 17th to 19th January 2012, a group of 92 college students and teachers attended a retreat in a hotel located on Pangkor Island, off the west coast of Peninsular Malaysia. Following the onset of symptoms in many participants who presented to our institute, an investigation was undertaken which ultimately identified Sarcocystis nesbitti as the cause of this outbreak. METHODOLOGY/PRINCIPAL FINDINGS: All retreat participants were identified, and clinical and epidemiological information was obtained via clinical review and self-reported answers to a structured questionnaire. Laboratory, imaging and muscle biopsy results were evaluated and possible sources of exposure, in particular water supply, were investigated. At an average of 9-11 days upon return from the retreat, 89 (97%) of the participants became ill. A vast majority of 94% had fever with 57% of these persons experiencing relapsing fever. Myalgia was present in 91% of patients. Facial swelling from myositis of jaw muscles occurred in 9 (10%) patients. The median duration of symptoms was 17 days (IQR 7 to 30 days; range 3 to 112). Out of 4 muscle biopsies, sarcocysts were identified in 3. S. nesbitti was identified by PCR in 3 of the 4 biopsies including one biopsy without observed sarcocyst. Non-Malaysians had a median duration of symptoms longer than that of Malaysians (27.5 days vs. 14 days, p = 0.001) and were more likely to experience moderate or severe myalgia compared to mild myalgia (83.3% vs. 40.0%, p = 0.002). CONCLUSIONS/SIGNIFICANCE: The similarity of the symptoms and clustered time of onset suggests that all affected persons had muscular sarcocystosis. This is the largest human outbreak of sarcocystosis ever reported, with the specific Sarcocystis species identified. The largely non-specific clinical features of this illness suggest that S. nesbitti may be an under diagnosed infection in the tropics.